Yirminci yüzyılın ekonomi yaklaşımları yaklaşımların dönüşümü-dönüştürülmesi ile ekonomik etkileri - Görenel, İlker Zeki (My University, 2004)
Doktora tezinin amacı 1980'li yıllarla birlikte küreselleşme dalgası içine giren ülke ekonomilerinde uygulanmaya başlanan, Washington Uzlaşısı içinde yer alan ekonomi politikalarının değerlendirilmesidir. Bu tür politikaların uygulanmasını gerekli kılan önceki döneme ait dinamiklerin saptanması ile birlikte politikaların uygulanışı, uygulama hataları, uygulama değişiklikleri göz önüne alınarak, yirmi beş yıllık süreç farklı ülke grupları açısından ele alınmıştır. Ekonomi politikalarının etkinliği odağa yerleştirilerek neoliberal ekonomi politikalarının ortaya çıkardığı sonuçlar belirlenmeye çalışılmıştır. Name and SurnameZeki İlker Görenel FieldEconomics ProgrammeEconomic Policy SupervisorProfessor F. Nuray Altuğ Degree Awarded and DatePhD 2004 KeywordsNeoliberal Economic Policies, Washington Consensus, Neoliberalism, Globalisation, Liberalisation

ECONOMIC APPROACHES OF TWENTIETH CENTURY THE TRANSFORMATION-CONVERSION OF THE APPROACHES AND THEIR ECONOMIC IMPACTS The purpose of the PhD thesis is the evaluation of the economic policies originated in Washington Consensus, and applied in the economies joined in the globalisation wave in the 1980s. The 25 year application period is undertaken according to the different country groups by determining the dynamics of the previous period and taking the application of the policies, application faults, application changes into the consideration. By focusing the efficiency of the economic policies, the outcomes of the neoliberal economic policies is tried to be determined.
Keywords: Ekonomi; Ekonomi Politikası